Answer:
[tex]t=\frac{\bar x_1- \bar x_2}{\sqrt{\frac{s_1^2}{n_1} +\frac{s_2^2}{n_2} } }[/tex]
Step-by-step explanation:
H0: µ1 – µ2 = 0
HA: µ1 – µ2 ≠ 0
We have given,
The population variances are not known and cannot be assumed equal.
The test statistic for the test is
[tex]t=\frac{\bar x_1- \bar x_2}{\sqrt{\frac{s_1^2}{n_1} +\frac{s_2^2}{n_2} } }[/tex]
Where,
[tex]\bar x_1[/tex] = sample meaan of population 1
[tex]\bar x_2[/tex] = sample mean of population 2
[tex]n_1[/tex] = sample size of population 1
[tex]n_2[/tex] = sample size of population 2
Therefore, this is the test
[tex]t=\frac{\bar x_1- \bar x_2}{\sqrt{\frac{s_1^2}{n_1} +\frac{s_2^2}{n_2} } }[/tex]